Attitudes toward the insanity defense: Examination of the factor structure of Insanity Defense Attitude-Revised (IDA-R) Scale in Ghana. - Adjorlolo, S.; Abdul-Nasiru, I.; Chan, H.C.; Bentum, F. (Taylor & Francis, 2016)
Decades of research have revealed the potential of individuals to be partial toward defendants pleading insanity at the time of offense. This study examines the internal structure of the Insanity Defense Attitude-Revised (IDA-R) scale as well as predictors of insanity defense attitude in a Ghanaian sample (N D 253). Using principal component analysis, we identified three distinct latent factors, two (i.e., strict liability, unprofessional behavior and safety concerns) of which corroborate the findings of previous studies, and a unique factor- expression of sympathy. Participants who were highly involved in religious activities were more likely to be sympathetic. Views regarding the causes and treatability of mental illness did not significantly predict insanity defense attitudes.
Journal Article
Keywords: Insanity defense attitude; juror bias; scale; factor structure; Ghana; Africa